Motorcycle workshop inventory management system with digital feedback - Muhamad Amin, Khairul Amir; Abu, Zurah (College of Computing, Informatics, and Mathematics, 2025)
Effective inventory management is essential for motorcycle workshops as it ensures the availability of necessary parts, optimizes stock levels, and enhances overall operational efficiency. In the context of Hairul Motor Service, a small motorcycle workshop, traditional manual inventory management methods have led to significant challenges such as inconsistent stock levels, difficulty in tracking customer and service records, and a lack of centralized feedback mechanisms. To address these issues, the project aims to develop a Motorcycle Workshop Inventory Management System with Digital Feedback. This system is designed to streamline inventory management, organize customer data, and facilitate efficient feedback collection through a digital platform. The project employs the Waterfall methodology to ensure a structured development process, progressing through stages of requirement gathering, design, implementation, testing, and maintenance. The findings from the implementation of this system indicate substantial improvements in inventory accuracy, reduction in stockouts, better customer service through organized data, and enhanced feedback collection and analysis. These outcomes demonstrate the system's effectiveness in addressing the workshop's operational challenges. The project concludes that adopting such a system can significantly optimize workshop operations, and it suggests ongoing monitoring, user training, and further system enhancements for sustained benefits. In the future, it is recommended to include integrating payment processing, linking with external systems, and incorporating robust data analytics tools to further improve efficiency and customer satisfaction.